Urban districts and drug scenes: a comparative study on nuisance caused by 'open' drug scenes in major European cities - Renn, Heinz (Office for Official Publications of the European Communities, 1996)
From the summary: Residents and tradespeople in selected districts of six major European cities were interviewed with standardized methods about the problem of nuisance caused by drug addicts appearing 'openly' in these districts: Amsterdam (three inner city districts), Rotterdam (four inner city districts), Hamburg (St.Georg district), Paris (Quartier 71 'La Goutte d'Or), London (district of Brixton in the Borough of Lambeth), Barcelona (Barrio 'El Raval'). In each district samples of approx. 200 residents and 50 tradespeople were interviewed. Moreover, about 50 local police officers were asked about complaints which had received from the general public. The fourth target group were drug addicts in the districts, who were inquired about their subcultural life style. Samples between 50 and 100 addicts were interviewed. A total of 2,217 persons were systematically examined. Also researchers had a look at the drug scenes in the districts under study.